Pelabelan Gender Perempuan Jawa dalam Novel Kartini dan Urgensinya untuk Pembelajaran Era Global - Haniah, Haniah; Waluyo, Herman J; Winarni, Retno (MUWAZAH, 2018)
Javanese  is one of the famous culture that owned by Indonesia. As one of the culture that enough reckoned , javanese had a wide range of science .Not only  the mosaic customs and any kind of a ceremony that he had, but the woman too. This study was a qualitative research aiming to describe negative labeling/ stereotype existing inside javanese women. Used a technique of analysis contents and interview, researchers will processing the data in the form of quotations novel with three stages: reduction , display data and data verification. The result of research showed that there were several negative labels. Firstly, men are considered as smarter than women, so that can be family’s more pride. Secondly, women having protruding breast are equivalent to ledhek or prostitute. Thirdly, gelung/sanggul (hair bun) is a symbol of women’s beauty. Fourthly, women producing sound of smacking lips during eating are just like animal. Fifthly, kitchen becomes basic standard of ability of taking care of husband and future household.  .As part of science, feminism need to introduced to school through language class. Keywords: Stereotype, Java’s woman, Kartini